Hidden labour: the skilful work of clinical audit data collection and its implications for secondary use of data via integrated health IT - Lynn McVey; Natasha Alvarado; Joanne Greenhalgh; Mai Elshehaly; Chris P. Gale; Julia Lake; Roy A. Ruddle; Dawn Dowding; Mamas Mamas; Richard Feltbower; Rebecca Randell (BMC, 2021)
Abstract Background Secondary use of data via integrated health information technology is fundamental to many healthcare policies and processes worldwide. However, repurposing data can be problematic and little research has been undertaken into the everyday practicalities of inter-system data sharing that helps explain why this is so, especially within (as opposed to between) organisations. In response, this article reports one of the most detailed empirical examinations undertaken to date of the work involved in repurposing healthcare data for National Clinical Audits. Methods Fifty-four semi-structured, qualitative interviews were carried out with staff in five English National Health Service hospitals about their audit work, including 20 staff involved substantively with audit data collection. In addition, ethnographic observations took place on wards, in 'back offices' and meetings (102 h). Findings were analysed thematically and synthesised in narratives. Results Although data were available within hospital applications for secondary use in some audit fields, which could, in theory, have been auto-populated, in practice staff regularly negotiated multiple, unintegrated systems to generate audit records. This work was complex and skilful, and involved cross-checking and double data entry, often using paper forms, to assure data quality and inform quality improvements. Conclusions If technology is to facilitate the secondary use of healthcare data, the skilled but largely hidden labour of those who collect and recontextualise those data must be recognised. Their detailed understandings of what it takes to produce high quality data in specific contexts should inform the further development of integrated systems within organisations.